Multiple roles of lymphatic vessels in tumor progression. (August 2018) - Ma, Qiaoli; Dieterich, Lothar C; Detmar, Michael
Highlights: Tumor lymphangiogenesis is associated with a poor prognosis in many cancer types. Lymphatic vessels provide a dissemination route for tumor cells. Lymphatic vessels potentially regulate tumor immunity. Lymphatic vessels might provide a 'lymphovascular' niche for stem-like tumor cells. Abstract : Sentinel lymph node metastasis is a prognostic indicator for systemic tumor spread in many types of cancers, and tumor lymphangiogenesis correlates with reduced survival. Consequently, lymphatic vessels have been suggested to promote tumor progression in multiple ways. Tumor lymphangiogenesis occurs both in primary tumors and at distant (pre-) metastatic sites, and facilitates lymphatic invasion and tumor cell dissemination. Lymphatic vessels have also emerged as regulators of tumor immunity, transporting tumor antigens to lymph nodes and directly interacting with immune cells. Furthermore, lymphatic vessels might provide a 'lymphovascular' niche contributing to the maintenance of stem-like tumor cells that are tightly related to tumor recurrence. Thus, targeting tumor lymphangiogenesis or specific lymphatic-associated functions might represent a promising approach to inhibit tumor progression.